2022
DOI: 10.3389/fmed.2022.850343
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Epithelial-Mesenchymal Transition-Related Long Non-coding RNA Prognostic Signature to Determine the Prognosis and Drug Treatment of Hepatocellular Carcinoma Patients

Abstract: IntroductionHepatocellular carcinoma (HCC) is one of the most common malignant tumors with poor prognosis. Epithelial–mesenchymal transition (EMT) is crucial for cancer progression and metastasis. Thus, we aimed to construct an EMT-related lncRNA signature for predicting the prognosis of HCC patients.MethodsCox regression analysis and LASSO regression method were used to build an EMT-related lncRNAs risk signature based on TCGA database. Kaplan-Meier survival analysis was conducted to compare the overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Another study suggested that a complex network consisting of 3 lncRNAs, 12 miRNAs, and 21 mRNAs may help in classifying patients into two subgroups and predicting HCC progression independently from TMB status [ 142 ]. Another study investigated the connection among single nucleotide polymorphisms (SNPs), TMB, and the epithelial–mesenchymal transition EMT-related lncRNAs, observing a specific signature to predict HCC prognosis, with high TMB and TP53 mutation associated with worse prognosis [ 143 ].…”
Section: Combination Of Tmb and Other Specific Genetic Biomarkersmentioning
confidence: 99%
“…Another study suggested that a complex network consisting of 3 lncRNAs, 12 miRNAs, and 21 mRNAs may help in classifying patients into two subgroups and predicting HCC progression independently from TMB status [ 142 ]. Another study investigated the connection among single nucleotide polymorphisms (SNPs), TMB, and the epithelial–mesenchymal transition EMT-related lncRNAs, observing a specific signature to predict HCC prognosis, with high TMB and TP53 mutation associated with worse prognosis [ 143 ].…”
Section: Combination Of Tmb and Other Specific Genetic Biomarkersmentioning
confidence: 99%
“…They showed that CDKN1A , TP53I3 , and PPM1D were upregulated by AL158206.1. Contrasting these findings, another work examining lncRNAs involved in the epithelial-mesenchymal-transition, associated with metastasis, identified AL158206.1 as one of four lncRNAs having the strongest negative impact on the survival of patients undergoing drug treatment of hepatocellular carcinoma ( 61 ). Interestingly, we observed upregulation of AL158206.1 and thus induction of protective radiation response after LDIR only in N1.…”
Section: Discussionmentioning
confidence: 99%
“…EV characteristic profiles had been postulated to provide insights into tumor behaviors. Previous research showed that PD1 and PD-L1 expression on melanoma-derived EVs predicted resistance to checkpoint inhibitors [ 54 ]; EV mRNA could predict NSCLC survival and efficacy of different treatment modalities [ 53 ]; long noncoding RNA may serve as a prognostic and immunotherapeutic predictor for testicular germ cell tumor and HCC [ 55 , 56 ]. Besides, EV DNA reflected both chromosomal and mitochondrial DNA of the original tumor, which could be a powerful tool to assess tumor genome and predict prognosis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%